Keluarga Dan Nilai Budaya Masyarakat Sunda Pada Perawatan Ibu Nifas Dan Bayi Baru Lahir - Giari Rahmilasari; Asri Tresnaasih; Reni Reni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to identify the Sundanese cultural value for family in mother’s postpartum care and new born baby Methods: Qualitative method was used in this study along with descriptive techniques to analyzed the data. Data mining is done using profound interview with four respondents who originally from the Sundanese tribe and live in Cipagalo village. Respondents are mothers who have two to six months old child.. Furthermore, the interview was also conducted with paraji as person who are still active giving services in the area. All data was collected by recording the conversations and based on the respondents’ consent. Next, the data were interpreted, reduced, and coded for final result. Analytical descriptive analysis was next conducted to this research findings using journals assessment. All findings were divided into three categories; useful findings, harmful findings, and insignificant findings. Useful findings are results that have scientific evidence and can be recommended to do. Harmful ones are things that are scientifically proofed to have harmful effect, whereas insignificant findings are results with unknown scientific proofs whether its harmful or not.Results: Results in this study showed various Sundanese cultural habits in Cipagalo village:(1) There are some forbidden food and beverages during the postpartum phase, including spicy, sour, and cold ones.(2) Suggestion to consume apple during the postpartum phase.(3) Herbs or traditional potion for postpartum. Herbs can be consumed in various ways like (a) boiling and drinking it, (b) grating and squeezing it, (c) boiling and using it to wash the private area (smeared).(4) Rest and sleep pattern. There is tradition which done by the mothers; they should not take a nap in the afternoon, afraid that the white blood cells would go up the eyes, or they could take a nap in a seated position with both toes tied together in hope it would help to tighten mom’s private area.(5) Clothes and mother’s care. There is a habit of using corset (stagen) or what they called bebengkung, soaking feet in warm water, and massaging mom’s body.(6) Massaging mom’s body. Not only massaging body parts, there is also massaging the uterus (disangsurkeun).(7) Baby care culture and traditional ceremonies. This includes placenta burial using spices or what the sundanese called as bali, baby girls circumcision and ear piercing.Conclusion: The habit of consuming apple, body massage, feet massage in warm water, the use of binahong leaves and ginger, handeuleum, and baby massage showed benefits not only for moms, but also babies during postpartum phase.